HASIL BELAJARA IPAS MELALUI MODEL PEMBELAJARAN PICTURE AND PICTURE (PAP) - Rizali, Ihsan; Hany Handayani; Asep Nurhuda; Annisa Nurfitriani; Atep Lesmana; Gemi Gustiani; Farah Naza Adilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
This study aims to describe the effect of the application of the Picture and Picture (PAP) learning model on the learning outcomes of IPAS elementary school students, especially grade IV at SDN 6 Sindangkasih Purwakarta Regency. This study used a preexperimental design with a one-group pretest-posttest type of research. The sampling technique used was saturated sampling type, because all populations were used as samples. The research instrument used was a test question in the form of a description. The research data were statistically analyzed through normality test, homogeneity test, and Paired Sample Test. Based on the results of the research conducted, the Picture and Picture learning model on the learning outcomes of IPAS elementary school students can be said to have an effect.